2008
DOI: 10.1038/jhh.2008.4
|View full text |Cite
|
Sign up to set email alerts
|

Changes of central haemodynamic parameters during mental stress and acute bouts of static and dynamic exercise

Abstract: Chronic dynamic (aerobic) exercise decreases central arterial stiffness, whereas chronic resistance exercise evokes the opposite effect. Nevertheless, there is little information available on the effects of acute bouts of exercise. Also, there is limited data showing an increase of central arterial stiffness during acute mental stress. This study aimed to determine the effect of acute mental and physical (static and dynamic exercise) stress on indices of central arterial stiffness. Fifteen young healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 50 publications
(66 reference statements)
3
28
0
Order By: Relevance
“…The reasons for this are not entirely clear but are in line with some previous studies that have reported increases in AIx during forearm exercise (3,5,10), probably due to increased sympathetic activity. This contrasts with other studies of whole body exercise, which have typically reported decreased AIx during exercise (7,12,13).…”
Section: Discussionsupporting
confidence: 73%
“…The reasons for this are not entirely clear but are in line with some previous studies that have reported increases in AIx during forearm exercise (3,5,10), probably due to increased sympathetic activity. This contrasts with other studies of whole body exercise, which have typically reported decreased AIx during exercise (7,12,13).…”
Section: Discussionsupporting
confidence: 73%
“…The studies described by Lydakis et al 10 and McEniery et al 18 have demonstrated the proof of the concept that PTT could be estimated from the measurement of a single aortic pulse wave. They showed that the inflection point could be identified by waveform analysis of the aortic pressure pulse.…”
Section: Discussionmentioning
confidence: 90%
“…PTT has also been estimated from the time of the inflection point in the aorta. 10 For aortic pressure pulses are estimated from radial tonometry pulses with the use of a generalized transfer function, 7,11,12 it raises the possibility that PTT could be derived directly from radial arterial pulses and provided equivalent information to aortic PTT. The study of Millasseau et al 13 suggested that similar information on the aortic pressure wave could be obtained directly from the radial pulse.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The travel time has also been estimated from the time of the inflection point, ie, the start of pressure augmentation, in proximal aortic pressure. 8,[12][13][14] This time of return, derived from aortic or carotid pressure has been used to estimate aortic pulse wave velocity (PWV) 10,11,[13][14][15] as a measure of aortic stiffness. Assuming that the major refection site is located at the lower abdominal aorta, twice this length (2L) divided by the time of return of the reflected wave (⌬t), ie, 2L/⌬t, has been taken equal to aortic PWV.…”
mentioning
confidence: 99%